2019
DOI: 10.3892/mmr.2019.10712
|View full text |Cite
|
Sign up to set email alerts
|

ST3Gal3 confers paclitaxel‑mediated chemoresistance in ovarian cancer cells by attenuating caspase‑8/3 signaling

Abstract: The aberrant expression of sialyltransferase has a role in cell differentiation, neoplastic transformation and the progression of various types of cancer. Our previous studies have shown that high expression of β-galactoside-α2,3-sialyltransferase III (ST3Gal3) in the metastatic ovarian cancer cell line HO8910PM attenuated cisplatin-induced apoptosis. The present study demonstrated that paclitaxel-induced chemoresistance in ovarian cancer cells upregulated the expression of ST3Gal3 and reduced the activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…In this regard, Yoshihama et al [ 8 ] also reported that the KD of ST3GAL4 in lung metastatic H1299 cells inhibit sLe x expression reducing cell adhesion to HUVEC cells, which suggests its potential as a target for cell metastasis. In ovarian cancer, ST3GAL3 KD sensitized ovarian cancer cells to cisplatin and paclitaxel induced apoptosis [ 55 , 56 ]. Intriguingly, the induction of epithelial-mesenchymal transition (EMT) in colon cancer led to the upregulation of FUT3, ST3GAL3 and ST3GAL4, which are implicated in the final steps of the biosynthesis of sLe x/a , suggesting a significant link between those Lewis antigens and EMT in colon carcinoma [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Yoshihama et al [ 8 ] also reported that the KD of ST3GAL4 in lung metastatic H1299 cells inhibit sLe x expression reducing cell adhesion to HUVEC cells, which suggests its potential as a target for cell metastasis. In ovarian cancer, ST3GAL3 KD sensitized ovarian cancer cells to cisplatin and paclitaxel induced apoptosis [ 55 , 56 ]. Intriguingly, the induction of epithelial-mesenchymal transition (EMT) in colon cancer led to the upregulation of FUT3, ST3GAL3 and ST3GAL4, which are implicated in the final steps of the biosynthesis of sLe x/a , suggesting a significant link between those Lewis antigens and EMT in colon carcinoma [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the expression of ST3GAL3 in breast cancer was found to be associated with poor prognosis (90). ST3Gal3 has also been associated with paclitaxel and cisplatin resistance in ovarian cancer cells (91,92).…”
Section: St3gal3mentioning
confidence: 99%
“… 30 Furthermore, the endocervical adenocarcinoma cell lines HO‐8910 (HeLa derivative) and HO‐8910 PM (HeLa derivative) expressed increased mRNA levels of ST3Gal‐3 and were more frequently resistant to chemotherapy medications cisplatin and paclitaxel when compared to SK‐OV‐3 cells, with low mRNA levels of α2,3‐sialyltransferase. High dose cisplatin could downregulate ST3Gal‐3 mRNA expression levels and enhance the number of apoptotic cells in both SK‐OV‐3 and HO‐8910 PM cells 42,60,61 . A study of Wichert et al found the correlation between high ST6Gal‐1 mRNA levels and lymphovascular invasion and reduced survival 32 …”
Section: Resultsmentioning
confidence: 99%